I never knew what time it was - Antin, David (University of California Press, 2005)
"In this series of intricately related texts, internationally known poet, critic, and performance artist David Antin explores the experience of time-how it's felt, remembered, and recounted. These free-form talk pieces-sometimes called talk poems or simply talks-began as improvisations at museums, universities, and poetry centers where Antin was invited to come and think out loud. Serious and playful, they move rapidly from keen analysis to powerful storytelling to passages of pure comedy, as they range kaleidoscopically across Antin's experiences: in the New York City of his childhood and youth, the Eastern Europe of family and friends, and the New York and Southern California of his art and literary career. The author's analysis and abrasive comedy have been described as a mix of Lenny Bruce and Ludwig Wittgenstein, his commitment to verbal invention and narrative as a fusion of Mark Twain and Gertrude Stein. Taken together, these pieces provide a rich oral history of and critical context for the evolution of the California art scene from the 1960s onward."--